WORK-LIFE BALANCE KONSULTAN PAJAK DI KANTOR KONSULTAN “X” DI SURABAYA - Thalia Febiola Putri Sunardi; Yenny Sugiarti (Akuntansi dan Teknologi Informasi, 2019)
This study aims to determine the work-life balance and worker satisfaction for his work as a tax consultant. Factors that can affect the work-life balance are work environment, flexibility, financial factors, and work culture. The object of this research is “X” Tax Consultant Office in Surabaya. This study used qualitative methods using semi-structured interview and direct observation. Based on the result of interviews and observations obtained result that flexibility and work environment have a role in determining work-life balance this is also supported by work environment and work culture provided by “X” Tax Consultannt Office. The results showed that there were 2 conditions of work on tax consultants where there was a balance between work and personal life during the low season and imbalance during the peak season, however the consultants were satisfied with the overall work-life balance they were carrying out.